Một số bài tiếp theo:
Bài số 27: Giải pt: $9x^2-5x=(2-x)\sqrt{3x^2-8x+3}$
Bài số 28: Giải hệ pt: $\left\{\begin{matrix} x^3+2y^2-4y+3\\ x^2+x^2y^2-2y=0 \end{matrix}\right.$
Bài số 29: Giải hệ pt: $\left\{\begin{matrix} x^2+xy+2=3x+y\\ x^2+y^2=2 \end{matrix}\right.$
Bài số 30: Giải pt: $13\sqrt{x^2-x^4}+9\sqrt{x^2+x^4} =16$
Bài 30: ĐK: $0\leq X\leq 1$
$13\sqrt{x^2-x^4}+9\sqrt{x^2+x^4}=16\Leftrightarrow 13(\sqrt{x^2-x^4}-\frac{2}{5})+9(\sqrt{x^2+x^4}-\frac{6}{5})=0$
$\frac{13(5\sqrt{x^2-x^4}-2)}{5}+\frac{9(5\sqrt{x^2+x^4}-6)}{5}=0 \Leftrightarrow \frac{13(5\sqrt{x^2-x^4}-2)(5\sqrt{x^2-x^4}+2)}{5(5\sqrt{x^2-x^4}+2)}+\frac{9(5\sqrt{x^2+x^4}-6)(\sqrt{x^2+x^4}+6)}{5(\sqrt{x^2+x^4}+6)}=0$
$\Leftrightarrow \frac{13(5x^2-4)(1-5x^2)}{5(\sqrt{x^2-x^4})+2}+\frac{9(5x^2-4)(5x^2+9)}{5\sqrt{x^2+x^4}+6}=0\Leftrightarrow (5x^2-4)(\frac{13(1-5x^2)}{5(\sqrt{x^2-x^4})+2}+\frac{9(5x^2+9)}{5\sqrt{x^2+x^4}+6})=0$
$\Rightarrow ...$